The functions of facilitation in multi-stakeholder learning: Lessons learned from capacity development on value chains management in innovation platforms in Burkina Faso and Ghana - Cadilhon, Joseph J. (2013)
Innovation platforms are groups of individuals or stakeholder representatives with different backgrounds and interests. They come together to diagnose problems, identify opportunities, and find ways to achieve their goals. When innovation platforms are set up by development projects, their processes are usually facilitated by the support organization. This short story presents how the author’s facilitation allowed the multiple stakeholders within local community innovation platforms supported by a project in Ghana and Burkina Faso to share experiences and knowledge so as to develop their respective capacities in value chains’ management and analysis. The main lesson from this story is that when facilitation by the support organization effectively supports learning processes by the stakeholders, it helps bring about recognition that commitment and communication are essential to help smallholders benefit from value chains and the subsequent engagement of all stakeholders in a continuous learning process. In time, the members of the innovation platform will take the responsibility to carry out further knowledge sharing activities without project support.